Chaotic Dynamics in a Three Species Aquatic Population Model with Holling Type II Functional Response - Upadhyay, R. K. K. (Nonlinear Analysis: Modelling and Control, 2008)
A three-trophic model for marine community is proposed and investigated by means of numerical bifurcation analysis. The proposed model based on a modified version of the Leslie-Gower scheme, incorporates mutual interference in all the three populations and generalizes several other known models in the ecological literature. We investigate the dynamical behavior of the model system by considering the Holling type II functional response of toxin liberation process. Bifurcation diagram and two-dimensional parameter scan suggest that chaotic dynamics is robust to variations in toxin production by phytoplankton. Our study suggests that toxic substances released by TPP population may act as bio-control by changing the state of chaos to order. The mutual interference also induces chaos and acts as both stabilizing and destabilizing factors.